Information – A New Open Access Scientific Journal on Information Science, Information Technology, Data, Knowledge and Communication - Shu-Kun Lin (Information, 2010)
We plan to expand our Open Access publishing project to encompass additional fundamental areas in science and technology and to provide publication opportunities for scientists working in these areas. To achieve these goals, we are in the process of launching new journals. [...]